TES KETERAMPILAN PROSES SAINS: MULTIPLE CHOICE FORMAT - Fibrika Rahmat Basuki; Jufrida Jufrida; Wawan Kurniawan; Ismawan Prasetia Devi; Olva Fitaloka (Pendidikan Kimia Unimus, 2019)
The purpose of this study was to develop and validate a multiple choice science process skills test. This research was a mixed method using sequential exploratory design. The data collection phase was divided into two. The qualitative data collection phase includes the stages of designing a science process skills test (arranging the test objectives, determining the type of process skills to be assessed, making a question grid, writing questions, face validity, and revising the questions). Quantitative data collection includes empirical test questions in schools, analyzing item analysis, revising questions, and assembling questions into tests. The subjects of this study were evaluation experts, material experts and students of SMAN 5 Jambi City as many as 100 people. The collection instrument was in the form of a review sheet/validation test. Qualitative data were analyzed descriptively, and quantitative data were analyzed using the ANATES Program. The results of this research are multiple choice science process skills tests. The aspects of science process skills that are measured are observing, identifying variables, predicting, hypothesizing, relationships between variables, communicating, designing investigations, and concluding. Of the 25 items developed, 18 valid questions were obtained. Discrimination indeks on the questions that have been developed is enough 20%, good 16%, and very good 64%. The level of difficulty is easy 8%, medium 80% and difficult 12%. The reliability of the question is 0.93 which is classified as very high.